2021
DOI: 10.1097/anc.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Informed Discharge Preparedness Tools in the NICU

Abstract: Background: Few studies address preparing parents of neonatal intensive care unit (NICU) infants for infant discharge. Inadequate or ineffective parental preparedness for discharge can result in preventable emergency department and primary care visits. Parents' perceptions are needed to inform development and implementation of effective educational tools to improve parent discharge preparedness in the NICU. Purpose: To describe the perceptions of parents of recently discharged NICU infants regarding discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The same study also reported that parents with other children at home felt better prepared for their infant to be discharged from the NICU than first-time parents. 12 The point about siblings was in line with the findings of quantitative studies that were conducted with the parents of hospitalised children 6 and with mothers during the postpartum period. 14 The stress that parents experience when their infants are hospitalised has been well established.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The same study also reported that parents with other children at home felt better prepared for their infant to be discharged from the NICU than first-time parents. 12 The point about siblings was in line with the findings of quantitative studies that were conducted with the parents of hospitalised children 6 and with mothers during the postpartum period. 14 The stress that parents experience when their infants are hospitalised has been well established.…”
supporting
confidence: 58%
“…12,13 A qualitative study found that when infants stayed in NICUs for more than 50 days, their parents felt better prepared for them to be discharged than the parents of infants with a shorter NICU stay. 12 It may be that extended stays provide more time for healthcare staff to teach parents about their infant's specific care needs. The same study also reported that parents with other children at home felt better prepared for their infant to be discharged from the NICU than first-time parents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impact of having a previous NICU admission has not been explored to our knowledge in NICU transition literature, some studies have examined how parity impacts readiness for discharge and discharge-teaching needs. For example, a study by Mazur et al23 found that parents with other children at home were more prepared to care for their infant independently but may have less time to spend at the hospital. The study also reported how fathers, in particular, may be less present in the NICU if they have other children at home due to caregiving needs of those children 23.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Mazur et al23 found that parents with other children at home were more prepared to care for their infant independently but may have less time to spend at the hospital. The study also reported how fathers, in particular, may be less present in the NICU if they have other children at home due to caregiving needs of those children 23. Although both mothers and fathers in this study found having other children to be facilitating, these results point to the need for tailored information regarding this transition.…”
Section: Discussionmentioning
confidence: 99%